2013
DOI: 10.1080/17429145.2013.845917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous nitric oxide on photosynthesis, antioxidative ability, and mineral element contents of perennial ryegrass under copper stress

Abstract: A hydroponics experiment was conducted to test the effects of sodium nitroprusside (SNP, a donor of NO) supplied with different concentrations on copper (Cu) toxicity in ryegrass seedlings (Lolium perenne L.). Excess Cu (200 µM) reduced chlorophyll content, resulting a decrease in photosynthesis. Cu stress induced the production of hydrogen peroxide (H 2 O 2) and superoxide anion (O 2 • −), leading to malondialdehyde (MDA) accumulation. Furthermore, activities of antioxidant enzymes in Cu-treated seedlings suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 48 publications
9
29
0
Order By: Relevance
“…In the current experiment, a similar increasing trend in cellular GB, proline, and total soluble protein contents was observed in both studied wheat cultivars as a result of exogenously applied SNP, H 2 O 2 , and SNP + H 2 O 2 as seed primers, which induced a greater protection to plants under stressed conditions. NO-induced enhanced accumulation of these osmolytes correlates well with the findings for several plant species that have already been studied [44,91,92]. As a ROS scavenger, proline acts as a non-enzymatic antioxidant of 1 O 2 and OH.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the current experiment, a similar increasing trend in cellular GB, proline, and total soluble protein contents was observed in both studied wheat cultivars as a result of exogenously applied SNP, H 2 O 2 , and SNP + H 2 O 2 as seed primers, which induced a greater protection to plants under stressed conditions. NO-induced enhanced accumulation of these osmolytes correlates well with the findings for several plant species that have already been studied [44,91,92]. As a ROS scavenger, proline acts as a non-enzymatic antioxidant of 1 O 2 and OH.…”
Section: Discussionsupporting
confidence: 82%
“…Nitric oxide has the potential to decrease the levels of H 2 O 2 and lipid peroxidation under water stress [43]. Exogenously-applied nitric oxide (NO) also improves the plant biomass production and leaf chlorophyll biosynthesis by improving the activities of antioxidants to reduce the damages caused by oxidative stress [44,45]. Nitric oxide signaling also plays an important role in plant disease resistance [46] in response to several abiotic stresses [5,7,8,47].…”
Section: Introductionmentioning
confidence: 99%
“…SNP application also has some positive role in improving the activity of Rubisco enzyme and ultimately enhancing photosynthetic activity. The study is supported by numerous findings such as protection of chlorophyll damage and enhancement in photosynthetic pigments in NO-treated Lolium perenne under Cu stress [61], Helianthus annuus exposed to Cd stress [62], Triticum aestivum [63], B. juncea under salt stress [54]. Treatment of cucumber seedlings, with SNP enhanced the chlorophyll content, rate of photosynthesis, and transpiration rate and stomatal conductance [64].…”
Section: Discussionsupporting
confidence: 65%
“…It was reported that signal messengers such as NO, hydrogen sulfide (H 2 S) and glycinebetaine (GB) play crucial roles in alleviating cadmium and Cu-induced damages in bermudagrass and perennial ryegrass [59,66,67]. Investigation of perennial ryegrass showed that NO could increase Cu accumulation in roots rather than in leaves [68]. Moreover, the rare element cerium (Ce) was reported to improve the copper tolerance of Poa pratensis by regulating ascorbate and glutathione metabolism pathways [61].…”
Section: Heavy Metal Stressmentioning
confidence: 99%